2010
DOI: 10.1139/o09-166
|View full text |Cite
|
Sign up to set email alerts
|

MVP interacts with YPEL4 and inhibits YPEL4-mediated activities of the ERK signal pathway

Abstract: Human YPEL4 is a member of YPEL family. It contains a Yippee domain, which is a putative zinc-finger-like, metal-binding domain. The human YPEL4 gene maps to chromosome 11q12.1, is ubiquitously expressed in adult tissues, and encodes a nuclear protein of 127 amino acids, the function of which remains unknown. To gain insights into the cellular function of this protein, we searched for YPEL4-interacting proteins using a yeast two-hybrid screen. The major vault protein (MVP), a lung resistance associated protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 12 publications
0
33
0
Order By: Relevance
“…ERK1/2 binds to MVP, suggesting that vaults may serve as signaling scaffolds for ERK1/2 or in the transport of phospho-ERK1/2 to the nucleus (40). Bag3 has being shown to stabilize the interaction of ERK1/2 with Dual-specificity Phosphatase 1 in HUVECs and in this case, its removal resulted in G1 block not apoptosis implying its role is cell dependent (41).…”
Section: Discussionmentioning
confidence: 96%
“…ERK1/2 binds to MVP, suggesting that vaults may serve as signaling scaffolds for ERK1/2 or in the transport of phospho-ERK1/2 to the nucleus (40). Bag3 has being shown to stabilize the interaction of ERK1/2 with Dual-specificity Phosphatase 1 in HUVECs and in this case, its removal resulted in G1 block not apoptosis implying its role is cell dependent (41).…”
Section: Discussionmentioning
confidence: 96%
“…To our best knowledge, this is heretofore the first demonstration that MVP is specifically tied to some, but not all, of the MAPK pathways in macrophages. Previous investigations have shown that MVP can attenuate Src-and YPEL4-induced ERK activation (29,30). Clearly, this discrepancy reflects on not only the cell types, but also the complicated nature of intracellular signaling of which MVP is an intimate part.…”
Section: Discussionmentioning
confidence: 96%
“…The extract was adjusted to 40% sucrose by adding 2 ml of 80% sucrose, and a total volume of 4 ml was transferred to an ultracentrifuge tube and overlaid with 1 ml of 35,30,25,20,15, and 5% sucrose in MES buffer as above but minus the Triton X-100. All of the materials were kept at 0°C.…”
Section: Methodsmentioning
confidence: 99%
“…56 The product of MVP that also genetically interacts with LAT has been postulated to act as a scaffold that modulates MAPK/ERK signaling. 57,58 Evidence is accumulating that it might be involved in the regulation of important cell signaling pathways, including PI3K/AKT, based on the finding that MVP binds several phosphatases and kinases such as PTEN, 59 PTPN11 (tyrosine phosphatase SHP-2), 58 as well as MAPK3 58 itself. The activity of the PI3K was shown to be essential to the signaling capacity of LAT-mediated complexes.…”
Section: Discussionmentioning
confidence: 99%